Synthetic Tools that Enable Synthesis and Understanding of Bioactive Macrocycles - Yudin, Andrei K. (Synlett, 2022)
This article aims to summarizing the evolution of my lab’s research efforts in making and understanding peptide macrocycles. What started as a curiosity-driven investigation of amphoteric structures in multicomponent reactions, has turned into a sustained exploration of complex macrocyclic peptides. As part of this journey, my students and I have introduced new tools that enable chemical synthesis and property-driven optimization of cyclic peptides. These contributions are expected to be relevant in the areas of drug discovery and biological probe design.
Keywords: macrocycles; peptides; cellular permeability; heterocycles; amphoteric molecules